Peran Chatbot Dalam Mendukung Smart Service pada Smart Library - Shiddiq Sugiono (Perpustakaan Nasional RI, 2021)
Chatbot is a digital technology based on artificial intelligence that has been utilized by various libraries to support the efficiency of information services. The use of chatbots is considered capable of creating a smart library ecosystem so it is important to continue to be developed so that customers are satisfied with the information services provided. This study aims to provide an overview of the benefits that can be obtained by libraries from implementing chatbots to achieve the concept of a smart library. The method used in this study is a literature review from the Google Scholar and Scopus database. There are 5 articles as the main research data. The results show that there are at least 2 benefits that can be obtained from implementing chatbots in library information services, namely: personalized information services and integration of cyberspace with libraries. In personalized information services, customers can get information that suits their needs without having to be overwhelmed with unnecessary information. As for integrating cyber space with real life, customers are able to access services without having to come to the location. Efficiency is the key word in the use of technology to support library services. More in-depth empirical research on chatbots, especially in Indonesia, needs to be carried out to be able to develop and evaluate the use of this technology.